ETHICAL AND VALUES EDUCATION IN UNIVERSITIES FOR SUSTAINABLE NATIONAL DEVELOPMENT IN SOUTH-SOUTH NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2026)
This article critically examined the high regards of ethical and value education in universities for sustainable national development in South-South Nigeria as a driver and catalyst. The study was guided by five objectives and five research questions. The theoretical frameworks were Albert Bandura's Social Learning Theory in 1977 and Lawrence Kohlberg's Theory of Moral Development in 1984. This work dived into several conceptual frameworks such as the imperative, extent of integration, pedagogical approaches employed in delivering, current challenges, impacts and strategic framework on ethical and value education in universities for sustainable national development. It was argued that beyond technical skills and academic knowledge, the inculcation of strong ethical principles and moral values in university students is paramount for fostering responsible leadership, combating corruption, promoting social cohesion, and driving socio-economic progress. The article highlighted the current challenges faced in this regard and proposes actionable strategies for integrating and strengthening ethical and values education within the university curricula such as the General Studies like Philosophy and Logic, Nigeria people and culture, entrepreneurship and campus culture in South-South Nigeria. Conclusively, when the universities system intentionally cultivating a generation of graduates who are not only intellectually competent but also morally upright, universities can play an indispensable role in transforming the region and, by extension, the nation. Suggestively, this requires a concerted effort from all stakeholders – government, university administration, faculty, students, and the wider community – to prioritize, integrate, and consistently uphold ethical principles as the foundation for a prosperous and just society.